2000
DOI: 10.1111/1467-8608.00191
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural effects of corporate ethical codes: Empirical findings and discussion

Abstract: The use of corporate ethical codes has been increasing. It is argued that the use of ethical codes solely as an instrument in a company’s image management is morally questionable. Therefore, the introduction and use of ethical codes must have the intention of achieving behavioural change or the maintenance of already superior behaviour. This change or superior behaviour may apply to ethics in general, but also to the different sub‐structures of ethics, namely the areas of reliability ethics, human ethics, capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 9 publications
3
42
0
Order By: Relevance
“…The respondents were usually requested to select their preferred response to a set of hypothetical ethical dilemmas. For example, Marnburg (2000) tested differences in attitudes of employees in two groups of companies in Norway: those with and those without codes. He concluded that the empirical findings suggest that the existence of business codes did not have any attitudinal effects because the two groups did not respond differently to the presented dilemmas.…”
Section: Vignettesmentioning
confidence: 99%
See 2 more Smart Citations
“…The respondents were usually requested to select their preferred response to a set of hypothetical ethical dilemmas. For example, Marnburg (2000) tested differences in attitudes of employees in two groups of companies in Norway: those with and those without codes. He concluded that the empirical findings suggest that the existence of business codes did not have any attitudinal effects because the two groups did not respond differently to the presented dilemmas.…”
Section: Vignettesmentioning
confidence: 99%
“…Weak positive relationship Badaracco and Webb (1995), Beets and Killough (1990), Bruce (1994), Dubinsky et al (1992), Mathews (1987), Murphy et al (1992), Peppas (2003), Schwartz (2001), Stevens et al (2005), Stohs and Brannick (1999), Valentine and Barnett (2002), Weaver (1995), Weeks and Nantel (1992). No significant relationship Akaah and Riordan (1989), Allen and Davis (1993), Ashkanasy et al (2000), Brief et al (1996), Cabral-Cardoso (2004), Callan (1992), Chonko and Hunt (1985), Clark and Leonard (1998), Cowton and Thompson (2000), Diller (1999), Farrell et al (2002), Ford et al (1982), Harker and Harker (2000), Healy and Iles (2002), Hume et al (1999), Hunt et al (1984), Kohut and Corriher (1994), Marnburg (2000), Mathews (1987), McKendall et al (2002), Montoya and Richard (1994), Ryan (1994), Sims and Brinkmann (2003), Snell and Herndon (2000), Stevens (2004), Treviño et al (1999). Mixed results Adam and Rachman-Moore (2004), Brenner and Molander (1977), Higgs-Kleyn and Kapelianis (1999), …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, many scholars have argued that ethical codes have a limited impact on ethical behaviour in organizations. Although many companies have a code of conduct, many of them are merely paying lip service to the notion of encouraging ethical behaviour (e.g., Kjonstad and Willmott, 1995;Lindsay et al, 1996;Marnburg, 2000;O'Dwyer and Madden, 2006;Sims, 1991;Sims and Brinkmann, 2003;Weaver et al, 1999). Others (e.g., Brinkmann and Ims, 2003) have argued that the effectiveness of ethical codes depends on the method of implementation, the process of code revision, the existence of disciplinary procedures in case of violations and the procedures in place for seeking advice or reporting violations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The effectiveness of the corporate code of ethics has been widely examined by many researchers (e.g. Marnburg, 2000;Schwartz, 2001;Sims & Brinkmann, 2003;McClearn, 2004). Despite research disagreement about the impact of code of ethics on the behavior of organizations, it is agreed that codes of ethics can be useful for decision making.…”
Section: Introductionmentioning
confidence: 99%